2014
DOI: 10.1111/j.1728-4457.2014.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Causes of Death in Low‐Mortality Countries: Implications for Mortality Projections

Abstract: This study examines the potential role that information about trends in causes of death could have in improving projections of mortality in low‐mortality countries. The article first summarizes overall trends in mortality by cause since the middle of the twentieth century. Special attention is given to the crucial impact of the smoking epidemic on mortality and on cause‐of‐death patterns. The article then discusses the implications for projections and reaches two conclusions. First, mortality projections can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
2
27
0
4
Order By: Relevance
“…Mortality by heart disease is 54% and 12% higher in the United States than in Costa Rica for men and women, respectively. These results point to smoking as an important explanatory factor of low adult mortality of Costa Rica, as it has been in other international comparisons of mortality (20,29). Using the epidemiological method proposed by Peto et al (30) to estimate smoking-related mortality under the assumption that lung cancer mortality is a reliable marker of the cumulative damage of smoking exposure, we estimate that if smoking was eradicated, the advantage in cardiovascular mortality of Costa Rica over the United States would disappear for men, and it would reverse into a 34% disadvantage for Costa Rican women.…”
Section: Discussionsupporting
confidence: 69%
“…Mortality by heart disease is 54% and 12% higher in the United States than in Costa Rica for men and women, respectively. These results point to smoking as an important explanatory factor of low adult mortality of Costa Rica, as it has been in other international comparisons of mortality (20,29). Using the epidemiological method proposed by Peto et al (30) to estimate smoking-related mortality under the assumption that lung cancer mortality is a reliable marker of the cumulative damage of smoking exposure, we estimate that if smoking was eradicated, the advantage in cardiovascular mortality of Costa Rica over the United States would disappear for men, and it would reverse into a 34% disadvantage for Costa Rican women.…”
Section: Discussionsupporting
confidence: 69%
“…Although the validity of routinely monitored health data by health system employees has been continuously questioned, if it is handled well like the one in urban Maharashtra, it will be a permanent solution to the problem. Though sample vital registration, when applied in conjunction with validated verbal autopsy procedures and medical record review, represents an affordable and cost-effective method, it is only a short-and medium-term solution to this problem [32,33]. Therefore, better systems for reporting, surveillance and monitoring of mortality and CoD will be sustainable only if developed keeping in mind the existing monitoring protocol at the national, state and district levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, smoking-related death rates for females continued to increase, despite a decline in overall mortality, and seem to have peaked around 2010. Researchers have suggested that mortality projections may be improved by adjusting for these underlying trends in smoking-related mortality (Bongaarts, 2014;Janssen et al, 2013). Trends in smoking-related deaths in Australia and the viability of incorporating trends into projections could be investigated with a view to improve projections.…”
Section: Projections By Cause Of Deathmentioning
confidence: 99%
“…According to Bongaarts (2014), the agestandardised all-cause death rate attributable to smoking for males in low mortality countries declined from the mid-1980s, after increasing substantially from the 1950s. In contrast, the smoking-related death rate for females increased from 1955 to 2010, although it was only around half the level for males at 2010.…”
Section: Changing Sex Compositionmentioning
confidence: 99%
See 1 more Smart Citation